Anatomical structure of the blade in some aquatic plants - Rodica Bercu (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The article comprises the investigation of the lamina (floating or emerged leaves) structure in some aquatic plants living in the Danube Delta channels, lakes and other aquatic areas, namely: Butomus umbellatus L., Nuphar luteum (L.) Sibthorp & Smith. and Trapa natans L. Cross sections of Nuphar luteum (L.) Sibthorp & Smith. and Trapa natans L. lamina reveal almost the same succession of tissues, that is an upper epidermis, the mesophyll (an aerenchyma) and the lower epidermis. Several veins in the mesophyll are present. Transections of Butomus umbellatus L. blade exhibit a triangle-shaped leaf with a chlorenchymatous tissue and a large aerenchyma. In the mesophyll, a number of large and small vascular bundles are embedded. The close collateral vascular bundles are poorly developed (few xylem and phloem elements and protoxylem lacunas). Nuphar luteum mid rib vein are double mixed or fused, usually inversely oriented. The blade anatomical characteristics of all species are in accordance with their or free floating or emerged nature.